Noninvasive Risk Stratification for Nonalcoholic Fatty Liver Disease Among Living Liver Donor Candidates: A Proposed Algorithm. Issue 4 (13th December 2021) - Danis, Nilay; Weeks, Sharon R.; Kim, Ahyoung; Baghdadi, Azarakhsh; Ghadimi, Maryam; Kamel, Ihab R.; Saberi, Behnam; Woreta, Tinsay; Garonzik‐Wang, Jacqueline; Philosophe, Benjamin; Gurakar, Ahmet; Loomba, Rohit
Abstract : To reduce waitlist mortality, living donor liver transplantation (LDLT) has increased over the past decade in the United States, but not at a rate sufficient to completely mitigate organ shortage. As a result, there are ongoing efforts to expand the living liver donor pool. Simultaneously, the prevalence of nonalcoholic fatty liver disease (NAFLD) in the general population has increased, which has significant implications on the pool of potential living liver donors. As such, a clinical assessment algorithm that exhaustively evaluates for NAFLD and fibrosis is critical to the safe expansion of LDLT. An ideal algorithm would employ safe and noninvasive methods, relying on liver biopsy only when necessary. While exclusion of NAFLD and fibrosis by noninvasive means is widely studied within the general population, there are no well‐accepted guidelines for evaluation of living donors using these modalities. Here we review the current literature regarding noninvasive NALFD and fibrosis evaluation and propose a potential algorithm to apply these modalities for the selection of living liver donors.